Pengaruh Kepemilikan Institusional, Corporate Social Responsibility dan Agresivitas Pajak Terhadap Nilai Perusahaan - Dea Sekar Putri; Enan Trivansyah Sastri (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of institutional ownership, corporate social responsibility, and tax aggressiveness on firm value in Food and Beverage Sub-sector Companies listed on the Indonesia Stock Exchange in 2019-2023. This type of research is quantitative research with secondary data sources. The sample in this study were 21 companies with 5 years of observation obtained by purposive sampling method, so that the total observations obtained were 105 observation data. The data analysis method in this study uses descriptive statistical analysis, and multiple linear regression analysis. The test results in this study indicate partial hypothesis calculation that institutional ownership variables, and tax aggressiveness have no effect on firm value, while corporate social responsibility affects firm value. The results of this study simultaneously show that the variables of institutional ownership, corporate social responsibility, and tax aggressiveness simultaneously affect firm value. This research is expected to provide contribution benefits in the development of theories regarding institutional ownership, corporate social responsibility, and tax aggressiveness on firm value, and researchers suggest adding other independent variables in order to get better research results.